PENERAPAN METODE PEER FEEDBACK UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS IV DALAM PRESENTASI KELOMPOK DI SDN MUGARSARI - Alma, Alma Yulia; Deni Chandra; Febri Fajar Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Speaking skills are one of the essential aspects of learning Bahasa Indonesia in elementary school, as they play a significant role in supporting students' communication abilities. However, observations in Grade IV at SDN Mugarsari revealed that students’ speaking skills were still low, as indicated by difficulties in pronunciation, intonation, word choice, and low self-confidence. This was due to the lack of interactive learning methods. This study aims to improve the speaking skills of Grade IV students at SDN Mugarsari in Bahasa Indonesia lessons through the application of the peer feedback method. The research was conducted in two cycles using a Classroom Action Research (CAR) approach, which involved planning, implementation, observation, and reflection. In each cycle, learning activities focused on group presentations, with speaking skills assessed through performance tests. The results showed that the peer feedback method improved student participation and their ability to express opinions verbally. The study involved 24 Grade IV students at SDN Mugarsari. In the first cycle, 14 students met the learning criteria, increasing to 21 students in the second cycle. The learning mastery in the second cycle reached 87.5%, exceeding the success criterion of 80%. Therefore, it can be concluded that the application of the peer feedback method is effective in improving students’ speaking skills in Bahasa Indonesia lessons.